Novel Antimicrobial Indolepyrazines A and B from the Marine-Associated Acinetobacter sp. ZZ1275 - Anjum, Komal (Mar Drugs, 2019)
Two new alkaloids indolepyrazines A (1) and B (2) were isolated from the marine-derived Acinetobacter sp. ZZ1275. Their structures were elucidated through extensive nuclear magnetic resonance (NMR) spectroscopic analyses, high resolution electrospray ionization mass spectroscopy (HRESIMS) data, and electronic circular dichroism (ECD) calculation. Indolepyrazine A represents the first example of alkaloids with an indole-pyrazine-oxindole skeleton. Both 1 and 2 showed antimicrobial activities against methicillin-resistant Staphylococcus aureus, Escherichia coli, and Candida albicans with minimum inhibitory concentration (MIC) values of 12 μg/mL, 8–10 μg/mL, and 12–14 μg/mL, respectively.